Dunbar’s number in the design of the schools of future: A case study - González García, Samuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Robin Dunbar found a range that was useful to quantify the number of individuals that could be part of a community whose members could know the rest of the community and keep relevant relationships with these other members. This study shows the evolution of a school from 3 to 18 years old that applied the Dunbar’s Number in its design and reviews the changes in the number of students, the perceived opportunities and advantages of applying this number in Education, besides of the evolution of the usage of this number in the school.